Strategi Diferensiasi Proses dalam Pencapaian Tujuan Merdeka Belajar pada Mata Pelajaran Pendidikan Agama Kristen - Rinaldus Tanduklangi (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
Process differentiation strategy-based learning is one part of the differentiation learning model which focuses on the learning processes and needs of different students. Process differentiation learning can be a relevant learning strategy in achieving the objectives of the Independent Learning Curriculum. This can be seen from the implementation of the process differentiation learning strategy which begins with building understanding, providing stimulus which culminates in a response in the form of exploring the material, giving assignments that are linked to individual learning needs of students, providing support in the assignment process, designing interesting learning activities. by accommodating the learning styles of students, as well as building flexible study groups according to students' abilities and interests. Stages like this are also a basic requirement in implementing Christian Religious Education (PAK) learning so that each student can achieve maximum learning goals. The research method used is qualitative descriptive research through library study, namely exploring references such as books and journals that are relevant to the topic being studied.